The problems of learning the Arabic verbal system among the Malay learners in Malaysian Universities - Ali, Asem Shehadeh Saleh (2013)
This study attempts to look into and analyze through Error Analysis the occurrences of linguistic errors among Malay students of Arabic in the use of the verbal system of Arabic. The Introduction highlights some issues and concepts pertinent to second/foreign language learning acquisition, as well as their implications to teaching. This study analyzes through Error Analysis the identified errors committed by a group of Malay learners of Arabic. Interferences from the mother tongue are also analyzed. The conclusion and recommendations are made based on the findings of this study with the aim of helping students in the learning of the target language. Keywords: The Subjects, the Test, Analysis, Summary.